'Standing up for Myself' (STORM): Development and qualitative evaluation of a psychosocial group intervention designed to increase the capacity of people with intellectual disabilities to manage and resist stigma. Issue 6 (4th July 2022) - Scior, Katrina; Cooper, Rebecca; Fenn, Kristina; Poole, Laurie; Colman, Sophie; Ali, Afia; Baum, Sandra; Crabtree, Jason; Doswell, Sophie; Jahoda, Andrew; Hastings, Richard; Richardson, Lisa
Abstract: Background: People with intellectual disabilities are at risk of experiencing stigma and require the skills and confidence to deal with stigma in their daily lives. Method: Development and piloting of a 5‐session manualised psychosocial group intervention designed to increase the capacity of people with intellectual disabilities aged 16+ to manage and resist stigma. Ten pre‐existing groups ( N  = 67) in third sector and education settings participated. Interviews with participants ( n  = 26), facilitators ( n  = 9) and significant others ( n  = 7) 2–4 months after the intervention assessed perceived impact. Results: Perceived benefits of the intervention for participants included increased understanding, improved connections with others, drive for advocacy, increased activity and self‐efficacy, and opportunity to process difficult events and emotions. Differential impact depending on individuals' pre‐existing self‐advocacy skills was noted. Conclusions: This early‐stage study indicates that further evaluation is merited to examine feasibility and outcomes of the STORM intervention.